The quality of life of disease-free Brazilian breast cancer survivors - Priscila Bernardina Miranda Soares; Jair Almeida Carneiro; Leandro Augusto Rocha; Renata Cristina Ribeiro Gonçalves; Daniella Reis Barbosa Martelli; Marise Fagundes Silveira; Hercílio Martelli Júnior
The objective of this study was to compare the quality of life of women who survived breast cancer and women who have not had the disease, and to identify associated factors. It is cross-sectional study in which the comparison group includes survivors of breast cancer aged between 40 and 69 years. One hundred and fifty-four women were included, 70 with breast cancer and 84 without the disease. The SF-36 was used to evaluate quality of life. The chi-square test and multivariate linear models were used to compare the groups. The estimated mean physical and mental components were significantly better for the group who survived the disease (51.10 and 52.25, respectively) compared to the group without cancer (47.26 and 47.93, respectively). The study indicates that survivors of breast cancer had a better quality of life compared to women without the disease.